Confirmed enterovirus encephalitis with associated steroid-responsive acute disseminated encephalomyelitis: An overlapping infection and inflammation syndrome. (March 2015) - Pillai, Sekhar; Tantsis, Esther; Prelog, Kristina; Ramanathan, Sudarshini; Webster, Richard; Ouvrier, Robert A.; Kesson, Alison; Brilot, Fabienne; Dale, Russell C.
Abstract: Background: Inflammatory disorders of the central nervous system have generally been separated into infectious or immune-mediated aetiologies. However, there are emerging examples of confirmed infectious viral infection of the brain followed by secondary inflammation or autoimmunity that is amenable to immune suppressive therapies. Methods: We report four children with confirmed enterovirus encephalitis (CSF enterovirus PCR positivity), who had MRI evidence of inflammatory demyelination compatible with ADEM. Results: Two patients had a monophasic course, whereas two had a biphasic course. Serum myelin oligodendrocyte glycoprotein antibodies were negative in two tested patients, although all patients had mirrored CSF and serum oligoclonal bands. All four patients only improved with introduction of immune therapy (corticosteroids in three, corticosteroid and intravenous immunoglobulin in one). Conclusion: These cases provide a further example of the overlap between CNS infection and immune mediated CNS disease. Randomised controlled trials investigating immune therapies in encephalitis are required.